Antihypercholesterolemia Effectiveness Test of Ceremai Leaf Ethanol Extract (Phyllanthus Acidus (L.) Skeels) on Male White Rats (Rattus Norvegicus) - Gunawan, Muhammad; Tanjung, Siti Aisyah; Fitriani, Enny; Safriana, Safriana (PT Inovasi Pratama Internasional, 2025)
Cholesterol is an increase in blood fat levels that can cause various heart diseases. Ceremai is one of the plants that some Indonesian people use to treat high blood pressure, diabetes mellitus and high cholesterol levels. This study aims to determine the effectiveness of ethanol extract of ceremai leaves in reducing blood cholesterol levels in male white mice with hypercholesterolemia. The inducers given to the test animals were 4 ml of quail egg yolk and propylthiouracil mixed with drinking water ad libitum. This study is an experimental study using 20 mice and divided into 5 groups. Group I (solvent control) CMC 0.5%, group II (comparison), group III, group IV and V (treatment) ethanol extract of ceremai leaves at a dose of 0.15, a dose of 0.3 and 0.6 g / KgBW. The extract was administered orally to the mice, and their cholesterol levels were measured on the 7th and 14th days after treatment. Cholesterol levels of each group were analyzed statistically using the One Way ANOVA method and Duncan's Post-Hoc test using SPSS 24.0. The results of statistical tests on blood cholesterol levels between simvastatin groups, ethanol extract of ceremai leaves showed a significant difference with an α value> 0.05. From the results of the study, it can be concluded that the ethanol extract of ceremai leaves has the activity of reducing blood cholesterol levels in male white rats induced by quail egg yolk and propylthiouracil with an effective EEDC dose of 0.3 g / kgBB.